Risk Factors for Revision After Artificial Urinary Sphincter Implantation in Male Patients With Stress Urinary Incontinence: A 10-Year Retrospective Study - Celeste Manfredi; Pramod Krishnappa; Esaú Fernández-Pascual; Elena García Criado; Diego Rengifo; David Vázquez Alba; Joaquín Carballido; Davide Arcaniolo; Juan Ignacio Martínez-Salamanca (International Neurourology Journal, 2022)
Purpose To evaluate the preoperative and intraoperative risk factors for revision after artificial urinary sphincter (AUS) implantation in male patients with stress urinary incontinence (SUI). Methods A retrospective analysis from a prospectively maintained database was performed. Male patients, with moderate-tosevere SUI, undergoing AUS implantation were included. All patients underwent placement of AMS 800. Cause of revision, type of revision, and time to revision were recorded. Multivariable analyzes were performed using a logistic regression to investigate the risk factors. Competing risk analysis according to Fine-Gray model was used to study time to event data. Results A total of 70 patients were included. Revision surgery was performed in 22 of 70 patients (31.4%), after a median (interquartile range) time of 26.5 months (6.5–39.3 months). Overall, 19 of 22 repairs (86.4%) and 3 of 22 explants (13.6%) were recorded. Mechanical dysfunction, urethral erosion, urethral atrophy, and device infection were the causes of revision in 11 of 22 (50.0%), 6 of 22 (27.3%), 3 of 22 (13.6%), and 2 of 22 patients (9.1%). Vesicourethral anastomosis stenosis (P=0.02), urethral cuff size of 3.5 cm (P=0.029), and dual implantation (P=0.048) were independent predictors for revision. Vesicourethral anastomosis stenosis (P=0.01) and urethral cuff size of 3.5 cm (P=0.029) predicted a lower survival of the AUS. Conclusions The vesicourethral anastomosis stenosis, urethral cuff size of 3.5 cm, and dual implantation are independent predictors for revision after AUS implantation. However, only the vesicourethral anastomosis stenosis and urethral cuff size of 3.5 cm predict a lower survival of AUS.